Analyzing The Effects Of Family, School, And Government Support On University Students’ Volunteering Intentions And Behaviors: A Case Study In Heilongjiang (International Journal of Environmental Sciences, 2025)
This study investigates the mechanisms through which family support, school support, and government support influence university students’ volunteering service behavior in Heilongjiang Province, China. Using partial least squares structural equation modeling (PLS-SEM), the research examined both direct and indirect pathways from social support variables to volunteering behavior, with volunteering service willingness as a potential mediator.The results reveal that only the path from volunteering service willingness (VSW) to volunteering service behavior (VSB) was statistically significant, highlighting the critical role of intention in predicting actual behavior. In contrast, direct effects from family support (FS), school support (SST), and government support (GS) on VSB were not significant. However, all three types of support showed significant indirect effects on VSB through VSW, confirming that volunteering service willingness fully mediates the relationship between social support and volunteering service behavior.These findings contribute to the literature on prosocial behavior by emphasizing the mediating role of psychological intention in the translation of support into action. Practically, the results suggest that to promote youth volunteerism, policymakers and educators should focus on cultivating students' willingness to volunteer by reinforcing supportive environments across family, school, and governmental domains.